2015
DOI: 10.1136/bmjopen-2014-006921
|View full text |Cite
|
Sign up to set email alerts
|

The Tanzanian trauma patients' prehospital experience: a qualitative interview-based study

Abstract: ObjectivesWe sought to characterise the prehospital experience of Tanzanian trauma patients, and identify barriers and facilitators to implement community-based emergency medical systems (EMS).SettingsOur study was conducted in the emergency department of an urban national referral hospital in Tanzania.ParticipantsA convenience sample of 34 adult trauma patients, or surrogate family members, presenting or referred to an urban referral emergency department in Tanzania for treatment of injury, participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 18 publications
8
59
0
Order By: Relevance
“…A systematic review of qualitative studies on maternal transport revealed eight major themes: time for transport, transport options, geography, local support, autonomy, culture, finance and ergonomics 21. A key recommendation was that clearer guidance should be provided to allow prioritisation of cases for emergency transport 11 12 21. Our study also revealed that errors in triage were key contributors to delays in transport.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A systematic review of qualitative studies on maternal transport revealed eight major themes: time for transport, transport options, geography, local support, autonomy, culture, finance and ergonomics 21. A key recommendation was that clearer guidance should be provided to allow prioritisation of cases for emergency transport 11 12 21. Our study also revealed that errors in triage were key contributors to delays in transport.…”
Section: Discussionmentioning
confidence: 68%
“…In a recent study which was a key driver to this work, Hodkinson et al 10 described a 12 month review of all patients admitted to the paediatric intensive care unit (PICU) at the Red Cross Children's Hospital, Cape Town; they found that 30% of PICU admissions were potentially avoidable. The study team identified that delays within the EMS system and poor prehospital clinical care were key contributors to the morbidity and mortality of critically ill and injured children A survey of LMIC EMS systems identified 22 barriers to prehospital care,6 and local studies in Gabon and Tanzania have identified barriers to EMS and areas for targets improvement 11 12. Identifying areas for focused quality improvement interventions can provide significant benefit, both in LMIC and high income settings 13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study represents one of the most comprehensive assessments of one-day trauma burden presenting to acute intake areas in districts and regional public hospitals of Tanzania. Most of the previous studies [ 19 , 20 , 24 ] had focused on the cities and areas with moderately- to highly-resourced hospitals, which left a gap in understanding the nature of injury and care in areas with different socio-economic settings. This study involved those areas but also many places not previously studied providing much-needed foundational knowledge of Tanzania’s trauma burden.…”
Section: Discussionmentioning
confidence: 99%
“…Most of RTI victims get to the hospital facilities from the scene through the efforts of untrained civilians and medically unknowledgeable lay responders such as police officers [ 7 , 8 ]. Although lay responders play a significant role in helping to transfer RTI victims from an accident scene to a health facility, they are generally not trusted by the victims to whom they provide care due to their low skills in managing casualties [ 9 ]. If effective care is to be provided, there is a need to strengthen the capacity of lay responders and for them to become competent in the provision of post-crash care [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%